ALK rearranged renal cell carcinoma (ALK-RCC): a multi-institutional study of twelve cases with identification of novel partner genes CLIP1, KIF5B and KIAA1217 - Kuroda, Naoto; Trpkov, Kiril; Gao, Yuan; Tretiakova, Maria; Liu, Yajuan J.; Ulamec, Monika; Takeuchi, Kengo; Agaimy, Abbas; Przybycin, Christopher; Magi-Galluzzi, Cristina; Fushimi, Soichiro; Kojima, Fumiyoshi; et al. (Modern Pathology, 2020)
ALK rearranged renal cell carcinoma (ALK-RCC) has recently been included in 2016 WHO classification as a provisional entity. In this study, we describe 12 ALK-RCCs from 8 institutions, with detailed clinical, pathological, immunohistochemical (IHC), fluorescence in situ hybridization (FISH), and next generation sequencing (NGS) analyses. Patients’ age ranged from 25 to 68 years (mean, 46.3 years). Seven patients were females and five were males (M:F = 1:1.4). Tumor size ranged from 17 to 70 mm (mean 31.5, median 25 mm). The pTNM stage included: pT1a (n = 7), pT1b (n = 1), and pT3a (n = 4). Follow-up was available for 9/12 patients (range: 2 to 153 months; mean 37.6 months); 8 patients were alive without disease and one was alive with distant metastases. The tumors demonstrated heterogeneous, ‘difficult to classify’ morphology in 10/12 cases, typically showing diverse architectural and cellular morphologies, including papillary, tubular, tubulocystic, solid, sarcomatoid (spindle cell), rhabdoid, signet-ring cell, and intracytoplasmic vacuoles, often set in a mucinous background. Of the remaining two tumors, one showed morphology resembling mucinous tubular and spindle cell renal cell carcinoma (MTSC RCC-like) and one was indistinguishable from metanephric adenoma. One additional case also showed a focal metanephric adenoma-like area, in an otherwise heterogeneous tumor. By IHC, all tumors were diffusely positive for ALK and PAX8. In both cases with metanephric adenoma-like features, WT1 and ALK were coexpressed. ALK rearrangement was identified in 9/11 tumors by FISH. ALK fusion partners were identified by NGS in all 12 cases, including the previously reported: STRN (n = 3), TPM3 (n = 3), EML4 (n = 2), and PLEKHA7 (n = 1), and also three novel fusion partners: CLIP1 (n = 1), KIF5B (n = 1), and KIAA1217 (n = 1). ALK-RCC represents a genetically distinct entity showing a heterogeneous histomorphology, expanded herein to include unreported metanephric adenoma-like and MTSC RCC-like variants. We advocate a routine ALK IHC screening for “unclassifiable RCCs” with heterogeneous features.
CRIS-Team Scopus Importer:2020-06-05